A systemic review and meta‐analysis exploring the predictors of sperm retrieval in patients with non‐obstructive azoospermia and chromosomal abnormalities. (2nd November 2021) - Majzoub, Ahmad; Arafa, Mohamed; Clemens, Hailey; Imperial, Jacqueline; Leisegang, Kris; Khalafalla, Kareim; Agarwal, Ashok; Henkel, Ralf; Elbardisi, Haitham
Abstract: To identify the most prevalent chromosomal abnormalities in patients with non‐obstructive azoospermia (NOA), consolidate their surgical sperm retrieval (SSR) rates and determine the significant predictors of positive SSR in this patient population. A systematic review and meta‐analysis were performed following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Fifty‐three studies including 2965 patients were identified through searching the PubMed database. Klinefelter Syndrome (KS) was the most prevalent chromosomal abnormality reported in 2239 cases (75.5%). Azoospermia factor c (AZFc) microdeletions were the second most common (18.6%), but men with these deletions had higher SSR rates than patients with KS (41.95% with AZFc vs. 38.63% with KS). When examining predictors of SSR in KS patients, younger age was a significant predictor of positive SSR in patients undergoing microsurgical testicular sperm extraction (micro‐TESE). Higher testosterone was a favourable predictor in those undergoing micro‐TESE and conventional TESE. Lower luteinizing hormone (LH) and follicular stimulating hormone (FSH) values were significantly associated with positive SSR with testicular sperm aspiration (TESA). No parameter predicted SSR rates in patients with AZFc microdeletions. Overall, genetic abnormalities have significant implications on SSR success in patients with NOA.